Estimation of the Lithuanian tax system according to J. Gill‘s diagnostic indices - Skačkauskienė, Ilona (Business, Management and Economics Engineering, 2010)
Theorists and practicians have various solutions on offer for estimating and improving the tax system. However, the tax system is a complicated combination, which calls for a systematic attitude and combined evaluation. In a specialized literature there can be found various offers of methodical nature for estimating tax systems, however, only few of the authors examine the tax system in a combined (complex) way. One of such authors is J. Gill. The aim of this examination is to evaluate the Lithuanian tax system by making use of J. Gill‘s diagnostic indices as well as to prove the suitability of the method for such a task. The tax system – by making use of J. Gill‘s method – has been evaluated, basing on the collection of revenues, under three aspects: natural qualities of tax system, efficiency and productivity. The qualitative and quantitative empiric examination disclosed merits and shortcomings of the Lithuanian tax system, and – with some exceptions – had proved the suitability of the method for evaluating tax systems. In the article there are also suggestions for improving of J. Gill‘s method.Article in Lithuanian.Lietuvos mokesčių sistemos vertinimas remiantis J. Gill diagnostiniais rodikliais